Cotinus coggygria scop. Attenuates acetic acid-induced colitis in rats by regulation of inflammatory mediators - ŞEN, ALİ; ERTAŞ, BÜŞRA; YILDIRIM, AYBENİZ; AKAKIN, DİLEK; BİTİŞ, LEYLA; ŞENER, GÖKSEL (My University, 2023)
In traditional medicine, many medicinal plants are used in the treatment of various diseases caused by infammation. The objective of the present study is to elucidate for the frst time the efects of Cotinus coggygria (CC) ethanol extract (CCE) on colonic structure and infammation of acetic acid-induced ulcerative colitis in rats. Colonic damage was assessed using disease activity index score, enzyme-linked immunosorbent assay, and hematoxylin–eosin staining. Also, in vitro antioxidant activity of CCE was investigated by ABTS methods. Total phytochemical content of CCE was measured spectroscopically. Acetic acid caused colonic damage according to disease activity index and macroscopic scoring. CCE signifcantly reversed these damages. While the levels of proinfammatory cytokines TNFalpha, IL-1beta, IL-6, and TGF-1beta increased in tissue with UC, IL-10 level decreased. CCE increased infammatory cytokine levels to values close to the sham group. At the same time, while markers indicating disease severity such as VEGF, COX-2, PGE2, and 8-OHdG indicated the disease in the colitis group, these values returned to normal with CCE. Histological research results support biochemical analysis. CCE exhibited signifcant antioxidant against ABTS radical. Also, CCE was found to have a high content of total polyphenolic compounds. These fndings provide evidence that CCE might be beneft as a promising novel therapy in the treatment of UC in humans due to high polyphenol content and justify the use of CC in folkloric medicine for treatment of infamed diseases.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Anti-infammatory activity; Antioxidant activity; Cotinus coggygria ethanol extract; Ulcerative colitis; Total phytochemical content